Penerapan Pendidikan Karakter dalam Pembinaan Akhlak Siswa MTs Nurul Khoiroh Tahun Pelajaran 2024/2025 - Dewi Utami Mahmuda; Vaesol Wahyu Eka Irawan; Hendro Juwono (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to describe the process of character development among students through the teaching of Akidah Akhlak subjects at MTs Nurul Khoiroh, and to identify and analyze the supporting and inhibiting factors in the implementation of character education at MTs Nurul Khoiroh. The approach used is descriptive qualitative, with data collection techniques including observation, in-depth interviews, and documentation. Informants in this study consist of the school principal, Akidah Akhlak subject teacher, vice principal for curriculum affairs, homeroom teachers, and students. The findings indicate that the teaching of Akidah Akhlak contributes significantly to student character formation, especially in instilling values such as honesty, responsibility, discipline, patience, and empathy. The character-building process is carried out through integrative and applicable learning approaches, habituation of positive behaviors, teacher role-modeling, and support from religious programs at the school. Supporting factors for successful character formation include the school’s commitment, a religious school environment, teacher role models, and active parental involvement. Meanwhile, the inhibiting factors encountered include the diverse backgrounds of students, limited instructional time, and negative influences from the environment and social media. The conclusion of this research shows that Akidah Akhlak learning is a strategic element in shaping students’ holistic character and should be continuously developed through synergy between schools, teachers, and families.